2015
DOI: 10.1051/matecconf/20153404003
|View full text |Cite
|
Sign up to set email alerts
|

Optimization of a neural network based direct inverse control for controlling a quadrotor unmanned aerial vehicle

Abstract: Abstract. UAVs are mostly used for surveillance, inspection and data acquisition. We have developed a Quadrotor UAV that is constructed based on a four motors with a lift-generating propeller at each motors. In this paper, we discuss the development of a quadrotor and its neural networks direct inverse control model using the actual flight data. To obtain a better performance of the control system of the UAV, we proposed an Optimized Direct Inverse controller based on re-training the neural networks with the n… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
1
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
1
1

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 12 publications
0
1
0
Order By: Relevance
“…Our research is based on a cross configuration of a quadcopter constructed in the Computational Intelligence and Intelligent Systems Laboratory, Universitas Indonesia. We previously also developed an NN-DIC scheme as a control system and optimized it to easily control the hovering state of the quadcopter (Heryanto et al, 2015). Our results showed that the optimized NN-DIC system improved the controller's performance, as indicated by a faster settling time compared with that of a non-optimized NN-DIC method.…”
mentioning
confidence: 86%
“…Our research is based on a cross configuration of a quadcopter constructed in the Computational Intelligence and Intelligent Systems Laboratory, Universitas Indonesia. We previously also developed an NN-DIC scheme as a control system and optimized it to easily control the hovering state of the quadcopter (Heryanto et al, 2015). Our results showed that the optimized NN-DIC system improved the controller's performance, as indicated by a faster settling time compared with that of a non-optimized NN-DIC method.…”
mentioning
confidence: 86%